PENGARUH KETERLIBATAN KERJA TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASI PADA BEBERAPA KANTOR DINAS DI KOTA BENGKULU - A Paryati; A Praningrum; Sugeng Susetyo (Management Insight: Jurnal Ilmiah Manajemen, 2018)
Abstract: The purpose of this study is examined the effect of job involvement on employees performance mediated with organizational commitment at some service office of Bengkulu city. This research was conducted at some service office of Bengkulu City. The object of research is the employees at some service office of Bengkulu City. Sample used in this study was 143 respondents using random sampling technique. Data analysis technique using multiple regression analysis with moderate variable and using SPSS 17.0 sofware. Research design using survey descriptive, the method  in this study using Pearson Correlation to test the validity of the data and using Cronbach's alpha to test the reliability of the data. The results of this research shows that the job involvement partially have positive and signifikan effect on employees performance, and organizational commitment was partial mediated the effect of job involvement on employees performance at some service office of Bengkulu city.Keywords : Job involvement, organizational commitment, employees performance